PENINGKATAN HASIL BELAJAR SISWA PADA MATERI PECAHAN MENGGUNAKAN MODEL PEMBELAJARAN THINK PAIR AND SHARE DI KELAS IV SDN 116 PALEMBANG - Diah Putri Islamy (PHI: Jurnal Pendidikan Matematika, 2023)
This study aims to improve student learning outcomes, especially in mathematics fraction material which so far students find it difficult and achieve less than optimal grades in fractional material. This research is a classroom action research that takes place in 2 cycles, in 6 meetings. Each cycle consists of 3 meetings. This study uses the Think, Pair and Share (TPS) learning model. The research was conducted on 35 grade IV students of SD Negeri 116 Palembang. The research data used observations on the observation sheet of student active participation activities and student learning outcomes in the form of solving LKS questions. The results showed that there was an increase in student learning outcomes in cycle 1 of 62.65 and in cycle 2 of 76.62. Student activity also increased as seen from the average student activity increased by 55.94 students out of the total.